The Drosophila doublesex proteins share a novel zinc finger related DNA binding domain. - Erdman, S.E.; Burtis, K.C. (The EMBO Journal, 1993)
The doublesex gene of Drosophila melanogaster is the final member of a well characterized hierarchy of genes that controls somatic sex determination and differentiation. The male-specific and female-specific doublesex polypeptides occupy a terminal position in the hierarchy, and thus regulate those genes responsible for the development of sexually dimorphic characteristics of the fly. To investigate the molecular mechanism by which these two related proteins interact with specific target genes, we have identified and characterized their DNA binding domains. Using gel mobility shift experiments with sequentially deleted polypeptides, site-directed mutagenesis and spectrophotometric assays, we have shown that the two doublesex proteins share a common and novel zinc finger-related DNA binding domain distinct from any reported class of zinc binding proteins. We have further shown that of 10 null dsx alleles, six encode proteins deficient in DNA binding activity, and that three of these alleles are the result of mutations that alter cysteine and histidine residues in the metal binding domain. Our results provide evidence that both the male-specific and female-specific doublesex proteins share and depend upon the same DNA binding domain for function in vivo, suggesting that both proteins bind to, but differentially regulate, a common set of genes in both sexes.